Pengaruh pendekatan deep learning dan media interaktif berbasis platform digital canva terhadap hasil belajar pengukuran luas di sekolah dasar - Yuni Karsih Asmi; Zainnur Wijayanto (Universitas Sebelas Maret, 2025)
The aim of this research is to knew the effectiveness of the Deep Learning approach using interactive learning media based on the Canva digital platform on students' mathematics learning result in the area measurement material. This research used a pre-experimental design method with a one group pretest–posttest design. The subjects research were one group of fourth-grade elementary school students who were given treatment, with measurements taken before and after treatment. The data analysis techniques used Pearson Product Moment correlation and comparative analysis using normalized gain (N-Gain). The results showed that there was a significant increase in student learning outcomes after the implementation of Deep Learning approach with the Canva-assisted . The average pretest score of 67.19 increased to 83.50 in the posttest. The results of the correlation test showed a significance value of 0.003, while the t-test results obtained a significance value of 0.001, which means there is a significant difference between the pretest and posttest results. The N-Gain value is in the moderate category with a score of 0.4232. These findings indicate that the Deep Learning approach with Canva assisted is effective in improving students' mathematics learning outcomes, especially in the area measurement material.